Transformation of the Chemical Industry Sector in Indonesia to Enhance Corporate Value - Adhar Putra Setiawan; Ma’ruf Sya’ban (BALANCE: Economic, Business, Management and Accounting Journal, 2026)
This study aims to analyze the transformation of the chemical industry sector in Indonesia in increasing company value. The independent variables include the Debt-to-Equity Ratio (DER) and stock price, with company size as a moderating variable. The study focused on 60 chemical industry companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The analytical method used was panel data regression. The results of the Chow and Hausman tests indicate that the Random Effect model is more appropriate, whereas the Lagrange Multiplier test supports the Fixed Effect model. The test results show that DER has no significant effect on company value, as measured by Price-to-Book Value (PBV). Meanwhile, stock price and company size have a negative and significant effect on PBV. In addition, company size cannot moderate the effect of DER on PBV, whereas it has been shown to moderate the effect of stock price on PBV. This study provides practical implications for chemical industry companies in increasing company value through effective management of capital structure, stock price movements, and company scale